Understanding Tourist Responsibility and Moral Reasoning in Small Island Ecotourism - Anak Agung Gde Raka Dalem; Ni Putu Ratna Sari (Yayasan Ghalih Pelopor Pendidikan, 2026)
Small islands are frequently promoted as ecotourism destinations due to their ecological sensitivity and bounded environments, yet little is known about how tourists interpret and negotiate ecological responsibility in these contexts. This qualitative study explores how tourists make sense of ecological responsibility during ecotourism experiences on small islands in Eastern Indonesia. Drawing on in depth interviews with twenty six foreign tourists across multiple island destinations, the study examines moments of environmental awareness, tensions between care and convenience, moral justifications, and perceptions of acceptable ecological impact. The findings show that ecological responsibility is not enacted as a fixed commitment but as a situational and negotiated process shaped by emotional responses, perceived constraints, and responsibility attribution. Tourists often engage in selective and symbolic sustainability practices that allow them to reconcile environmental concern with leisure expectations. By conceptualizing ecological responsibility as moral negotiation, this study contributes to sustainable tourism and ecotourism literature by offering a context sensitive understanding of how sustainability is interpreted and practiced in small island settings. The findings provide insights for designing ecotourism strategies that align ethical responsibility with visitor experience.